2009
DOI: 10.1016/j.cell.2008.12.002
|View full text |Cite
|
Sign up to set email alerts
|

PH Domain-Only Protein PHLDA3 Is a p53-Regulated Repressor of Akt

Abstract: p53 And Akt are critical players regulating tumorigenesis with opposite effects: whereas p53 transactivates target genes to exert its function as a tumor suppressor, Akt phosphorylates its substrates and transduces downstream survival signals. In addition, p53 and Akt negatively regulate each other to balance survival and death signals within a cell. We now identify PHLDA3 as a p53 target gene that encodes a PH domain-only protein. We find that PHLDA3 competes with the PH domain of Akt for binding of membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
220
2
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(243 citation statements)
references
References 36 publications
14
220
2
3
Order By: Relevance
“…Based on our results, we hypothesize that the regulation of Akt activation by CABYR-a/b is likely posttranslational, and this hypothesis is also supported by observations that gene amplification (data not shown) and total Akt protein levels do not change in CABYR-a/b-silenced cells compared with mock controls. One possible mechanism may be that CABYR-a/b indirectly regulates Akt dephosphorylation by modulating proteins that terminate Akt signaling through the dephosphorylation and inactivation of Akt, such as PHLPP (25), CTMP (26), PHLDA3 (27), and FKBP51 (28). Conversely, CABYR-a/b may also influence the activation of Akt directly or indirectly.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our results, we hypothesize that the regulation of Akt activation by CABYR-a/b is likely posttranslational, and this hypothesis is also supported by observations that gene amplification (data not shown) and total Akt protein levels do not change in CABYR-a/b-silenced cells compared with mock controls. One possible mechanism may be that CABYR-a/b indirectly regulates Akt dephosphorylation by modulating proteins that terminate Akt signaling through the dephosphorylation and inactivation of Akt, such as PHLPP (25), CTMP (26), PHLDA3 (27), and FKBP51 (28). Conversely, CABYR-a/b may also influence the activation of Akt directly or indirectly.…”
Section: Discussionmentioning
confidence: 99%
“…However, a role of PTEN as mediator of such p53-dependent inhibition of Akt phosphorylation can be excluded in our model of PTEN-deficient glioma cells. Whether or not PHLDA3, a further p53-regulated repressor of Akt identified very recently (32), contributes to the suppression of Akt phosphorylation in PTEN-deficient glioma cells irradiated in the presence of caffeine remains to be determined in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies on a closely related gene, Phlda3, suggest a role for these PH domain-only proteins in inhibiting Akt-regulated processes (Kawase et al 2009), this has not been formally demonstrated for Phlda2. Expression of Phlda2 in the placenta is first detected in the ectoplacental cone following implantation, becoming restricted to the syncytiotrophoblast of the labyrinth layer by E10.5 (Frank et al 1999).…”
Section: D13mentioning
confidence: 99%